Perspectives of Canadian fitness professionals on exercise and possible anorexia nervosa. Issue 1 (December 2015) - Wojtowicz, Amy; Alberga, Angela; Parsons, Colleen; von Ranson, Kristin
Abstract Background Many individuals with eating disorders, including anorexia nervosa (AN), engage in overexercise. Little is known about fitness professionals' perceptions of their responsibilities when interacting with clients with possible AN. The purpose of the current study was to examine Alberta fitness professionals' experiences with clients suspected of having AN, and their views on related ethical issues. Specifically, we aimed to examine (1) their experiences with fitness clients suspected of having AN; (2) their opinions about related ethical responsibilities of fitness professionals; and (3) their views on related training and ethical issues. Methods We administered a 21-item online survey to 143 Canadian fitness professionals about their experiences and perspectives on encountering individuals with possible AN in exercise classes and at their exercise facilities. Results Sixty-two percent of respondents had encountered a client they believed had AN. Three-quarters had never received any training on managing clients with AN and felt inadequately prepared for such situations. Although most felt ethically obliged to intervene with such a client, more than two-thirds reported no relevant guidelines in their professional training. Conclusions Many fitness professionals are faced with clients with possible AN, have the desire to help, feel ethically obligated to take action, but do not know what course of action to take, if any. Work is needed to clarify ethical issues and related training needs for certification programs for fitness professionals regarding AN.